Easily misdiagnosed intramuscular hemangioma: a case report. Issue 12 (December 2020) - Li, Yujia; Chou, Ke; Xiong, Jiepeng; Zhu, Wei; Yu, Min
An intramuscular hemangioma is a benign vascular tumor that often occurs in the lower extremities. We herein report a rare case of an intramuscular hemangioma that occurred in the gluteus medius muscle and was misdiagnosed as lumbar disc herniation. A 36-year-old woman presented with incidental and infrequent pain of the left buttock. She was diagnosed with lumbar disc herniation and underwent treatment. Although her pain was slightly relieved, relapse soon occurred. X-ray examination and magnetic resonance imaging revealed a mass in the gluteus medius muscle. The mass was suspected to be a malignant tumor and was therefore resected. The final diagnosis was an intramuscular hemangioma. Her pain completely disappeared thereafter and did not recur. Patients with intramuscular hemangiomas usually have no specific symptoms; therefore, this tumor is often misdiagnosed. When a satisfactory treatment effect is not obtained, the diagnosis should be reassessed in a timely manner.